2019
DOI: 10.1007/978-3-030-12075-7_21
|View full text |Cite
|
Sign up to set email alerts
|

Deep Unsupervised Learning for Condition Monitoring and Prediction of High Dimensional Data with Application on Windfarm SCADA Data

Abstract: In this work we are addressing the problem of statistical modeling of the joint distribution of data collected from wind turbines interacting due to collective effect of their placement in a wind-farm, the wind characteristics (speed/orientation) and the turbine control. Operating wind turbines extract energy from the wind and at the same time produce wakes on the down-wind turbines in a park, causing reduced power production and increased vibrations, potentially contributing in a detrimental manner to fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…In the offered case study, we demonstrated this idea on short‐term fatigue damage equivalent loads for wind turbines. Other wind‐energy related problems where CVAEs may find application are, for instance, wind farm level SCADA data modeling 48 or turbulence modeling 84,85 where finer turbulence scales are resolved in a data‐driven manner in place of the mostly empirical and mathematically simplified standard classical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the offered case study, we demonstrated this idea on short‐term fatigue damage equivalent loads for wind turbines. Other wind‐energy related problems where CVAEs may find application are, for instance, wind farm level SCADA data modeling 48 or turbulence modeling 84,85 where finer turbulence scales are resolved in a data‐driven manner in place of the mostly empirical and mathematically simplified standard classical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The VAE is used as a means of learning features from the monitoring data. In Mylonas et al 48 we have applied conditional variational autoencoders n the problem of modeling the SCADA summary statistics data, on a simulated wind farm, with the purpose of establishing VAEs as a tool for condition monitoring.…”
Section: Prior Related Work On Machine Learning and Probabilistic Techniques For Damage Monitoring And Remaining Useful Life Predictionmentioning
confidence: 99%
“…A very recent methodology StatFEM (Duffin et al, 2021;Girolami et al, 2021), provides an elegant Bayesian framework for both building and updating generative FE models. In terms of generative black-box models, GANs are by no means the only option; in fact, one alternative-the variational auto-encoder (Kingma and Welling, 2014)-has already proved to be generally useful in engineering problems; particularly in condition monitoring problems (e.g., Mylonas et al, 2020). Another versatile generative framework is provided by Gaussian processes (GPs) (Rasmussen and Williams, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At a supervisory control system, the major task of SCADA systems is to monitor a system's processes and apply the appropriate controls accordingly. SCADA systems are basically CPSs used in industries which included in a wide number of application areas [1][2][3][4].This solution present in the industry is Web SCADA, which provides multiple benefits that include anywhere/anytime accessibility to the system through a secure web browser connection. When the future Internet is considered, new technologies replace old technologies, hence, we can say that the integration of industrial business systems and the cloud concept has made the integrated SCADA systems more vulnerable compared with classical SCADA systems.…”
Section: Introductionmentioning
confidence: 99%